2015
DOI: 10.1007/s00408-015-9761-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Endobronchial Ultrasound-Guided Fine Needle Aspiration and Video-Assisted Mediastinoscopy for Mediastinal Staging of Lung Cancer

Abstract: Video-assisted mediastinoscopy (VAM) and endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) are the two most commonly used invasive methods for mediastinal staging of lung cancer. The objective of this review is to assess and compare the overall diagnostic values of VAM and EBUS-TBNA. PubMed, Embase, Web of Science and the Cochrane Library were searched for studies that evaluated EBUS-TBNA or VAM accuracy. Quantitative meta-analysis was used to pool sensitivity and specificity, and st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 33 publications
(55 reference statements)
0
39
0
9
Order By: Relevance
“…EBUS-TBNA performance in mediastinal LN staging in lung cancer has also been compared to that of Med, in prospective studies (19,20,35) (Table 1) and recently in a meta-analysis (56). Populations with moderate and high prevalence of mediastinal nodal metastasis were assessed (prevalence ranged from 32% to 89%).…”
Section: Ebus-tbna Vs Med: a Comparison Of Diagnostic Performance Inmentioning
confidence: 99%
See 1 more Smart Citation
“…EBUS-TBNA performance in mediastinal LN staging in lung cancer has also been compared to that of Med, in prospective studies (19,20,35) (Table 1) and recently in a meta-analysis (56). Populations with moderate and high prevalence of mediastinal nodal metastasis were assessed (prevalence ranged from 32% to 89%).…”
Section: Ebus-tbna Vs Med: a Comparison Of Diagnostic Performance Inmentioning
confidence: 99%
“…However, per LN analysis showed that EBUS-TBNA had higher diagnostic accuracy (91%) than Med (78%, P=0.007). Recently, a large meta-analysis was conducted comparing indirectly diagnostic yield of mediastinal staging with EBUS-TBNA to that of Med (56). Ten EBUS-TBNA and seven Med studies were included.…”
Section: Ebus-tbna Vs Med: a Comparison Of Diagnostic Performance Inmentioning
confidence: 99%
“…But, these new technologies are very expensive, they require highly trained personnel, and they are usually reserved for centers of excellence. Some of the techniques, especially after the recognition of high diagnostic yield and usefulness, should be made readily available even in less advanced centers [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective, crossover trial to compare the diagnostic yield of EBUS-TBNA and CMS was conducted by Ernst in 2008, and the results indicated that the yield of N staging accuracy was not different between two methods, but the sensitivity of EBUS-TBNA in lymph node station diagnosis was higher than that of CMS (25). Several systemic reviews also concluded that the pooled sensitivities of EBUS-TBNA and CMS had no significant differences, and both exhibited equally high diagnostic accuracy for mediastinal staging of lung cancer (20,26).…”
Section: Discussionmentioning
confidence: 99%